The Influence of Kidnapping and Banditry on Mathematics Achievement in Selected Secondary Schools in Zamfara compare to Gombe States - Hassan , Muhammad; Niyi , Olonrunsola Oriola; Ogbu, Angel Otse; Sadik , Hamagam (Kashere Journal of Education, 2025)
In conflict-affected regions, environmental insecurity presents a growing challenge to educational systems, but its implications for mathematics achievement in comparative contexts have not received enough attention. This study examined the influence of environmental insecurity – specifically, kidnapping and banditry – on senior secondary school students’ mathematics achievement in Nigeria, using a comparative analysis of Zamfara State (high insecurity) and Gombe State (relatively low insecurity). A comparative cross-sectional survey design was employed. Data were collected from 300 students and 36 mathematics teachers drawn from 18 public secondary schools using a Mathematics Achievement Test and an Environmental Insecurity Questionnaire. Descriptive statistics and Chi-square tests were used for analysis. The findings revealed a substantial and statistically significant disparity in mathematics achievement between the two states, with students in Zamfara recording markedly lower achievement than their counterparts in Gombe. Environmental insecurity was significantly associated with mathematics achievement, indicating that academic performance varied systematically by security context. The gender-disaggregated analysis revealed that Zamfara’s female students suffered more than male students, while Gombe showed no significant gender differences. Further analysis by school location indicated that rural schools experienced more severe learning disruptions than urban schools, although urban students were also affected, primarily through insecurity encountered during travel to school. The study finds that environmental insecurity negatively impacts math performance by disrupting teaching, affecting girls more, and putting rural students at a disadvantage. To improve education in Addressing educational underachievement in high-risk regions therefore requires integrated education and security interventions, with targeted support for rural schools and female learners.